A Sociological Approach to Consumer Protection in E-Commerce Transactions During the Covid-19 Pandemic - Dena Ayu; Mursal Mursal; Putri Jianti; Doli Witro; Rifqi Nurdiansyah (Khazanah Hukum)
This article uses a sociological approach to discuss consumer protection in the sales system through e-commerce during the covid-19 pandemic. This study aims to provide legal certainty to consumers by highlighting consumer protection laws and the role of the government in protecting people who make transactions in e-commerce. This article is juridical-normative research. This article uses qualitative data that is a literature study. In this case, two types of data are used: primary and secondary data. Primary data includes Law Number 8 of 1999 concerning Consumer Protection. At the same time, secondary data is obtained from library sources such as books, scientific articles, theses, dissertations, research reports, internet websites, and other data sources. Miles et al. used the qualitative data analysis technique, namely data condensation, data presentation, and concluding. The analysis results show that the consumer protection law does not only apply to consumers but to everyone who transacts in it. Consumer protection is very much needed to maintain security and provide convenience for sellers and buyers in carrying out economic transactions in the covid-19 pandemic. The role of law in consumer protection following the Consumer Protection Law Number 8 of 1999 provides efforts to ensure legal certainty to protect consumers.